The psychology of the value of human life: contingent moralities in enactments of violence in South Africa - Mwaikambo, Amina (My University, 2020)
When people have power and status, their lives are noticeable, they become relevant, and their lives tend to appear more valuable than others. In a country like South Africa that has been plagued by violence and competition for power, socio-political development has afforded some lives more access to resources and privilege, thus making those human positions more appealing than others. When violence happens to affluent individuals, society is more likely to be informed, make meaning of, or consider such violence as a tragedy. This research study intended to explore the judgments that tend to be made about the value of human life in South African society’s violent contexts. Drawing from psychological theory, and extracts from focus group discussions, thematic content analysis was conducted. Despite discourses of equality, it was concluded that some lives attract more attention and compassion in violent situations than others. In both everyday life, and in crisis situations, there are some human subjects that are deemed more important than others. These lives are the lives that are noticed, that evoke empathy, and are grieved when harm begets them. Analysis of the participants’ discussions highlighted how identities along the intersectionalities of gender, sexuality, age, class, race, and ability were key to determining the value of a person’s life. One’s positionality in society was analysed as a proxy through which human life was measured. It was concluded that the manner in which these identities intersect in each human body served as a contributor to how that particular life was perceived .It was also inferred that violence is enacted differently according to the statuses of people involved, and this ascertained whether the acts of violence were considered to be worthy of social outrage
A research report submitted to the Faculty of Humanities, at the University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Arts in Community-based Counselling Psychology, 2020